Profil Modalitas Belajar Peserta Didik untuk Pembelajaran Diferensiasi SDN Ngaliyan 01 - Fitri Mei Ambarwati; Nursiwi Nugraheni (Jurnal Pendidikan : Riset dan Konseptual, 2023)
The teacher needs to know the description of the tendency of the learning modality profile of class IV students at SD Negeri Ngaliyan 01. Information regarding the modality profile of students will influence the teacher's further steps in implementing differentiated learning. The research method is descriptive. The students who were used as the study were class IVC students with a total of 28 students. The purpose of this research is to know the learning modality and the results of the research show that the percentage of visual modality is 54%, auditory 18%, and kinestetic 28%. Different learning or differentiation is intended to bridge the diverse needs of students.